Nanobiomaterials' applications in neurodegenerative diseases. (February 2017) - Silva Adaya, Daniela; Aguirre-Cruz, Lucinda; Guevara, Jorge; Ortiz-Islas, Emma
The blood–brain barrier is the interface between the blood and brain, impeding the passage of most circulating cells and molecules, protecting the latter from foreign substances, and maintaining central nervous system homeostasis. However, its restrictive nature constitutes an obstacle, preventing therapeutic drugs from entering the brain. Usually, a large systemic dose is required to achieve pharmacological therapeutic levels in the brain, leading to adverse effects in the body. As a consequence, various strategies are being developed to enhance the amount and concentration of therapeutic compounds in the brain. One such tool is nanotechnology, in which nanostructures that are 1–100 nm are designed to deliver drugs to the brain. In this review, we examine many nanotechnology-based approaches to the treatment of neurodegenerative diseases. The review begins with a brief history of nanotechnology, followed by a discussion of its definition, the properties of most reported nanomaterials, their biocompatibility, the mechanisms of cell–material interactions, and the current status of nanotechnology in treating Alzheimer's, Parkinson's diseases, and amyotrophic lateral sclerosis. Of all strategies to deliver drug to the brain that are used in nanotechnology, drug release systems are the most frequently reported.